2021
DOI: 10.3390/antiox10091487
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin Ameliorates Vascular Dysfunction and Remodeling by Modulation of Nrf2/HO-1 and p-JNK/p-NF-κB Expression in Hypertensive Rats

Abstract: Diosmetin is a citrus flavonoid that has antioxidant and anti-inflammatory effects. This study examined the effect of diosmetin on blood pressure and vascular alterations and its underlying mechanisms in experimentally hypertensive rats. Male Sprague rats were administered Nω-nitro-L-arginine methyl ester L-NAME for five weeks and were given diosmetin at doses of 20 or 40 mg/kg or captopril (5 mg/kg) for two weeks. Diosmetin alleviated hypertension, improved endothelial dysfunction, and suppressed the overacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 64 publications
(83 reference statements)
1
22
0
Order By: Relevance
“…They are generally utilized as functional foods, soft drinks, and many other food items, and show good nutritional value [ 59 , 60 ]. In animal AsAA models, their action has been revealed to be effective, while human clinical trial studies have failed to demonstrate this evidence [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Davies and Holt, by adopting two modelling techniques, namely Gillespie’s Stochastic Simulation Algorithm (using Kinetiscope) and a discrete Markov chain, have showed the diverse reasons for this failure, including the rate of reaction between the free radicals and the non-enzymatic antioxidants, which is considered a necessary threshold for evaluating the effect of an antioxidant on the free radical defence systems naturally present, making it able to minimise their action [ 63 ].…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
See 1 more Smart Citation
“…They are generally utilized as functional foods, soft drinks, and many other food items, and show good nutritional value [ 59 , 60 ]. In animal AsAA models, their action has been revealed to be effective, while human clinical trial studies have failed to demonstrate this evidence [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Davies and Holt, by adopting two modelling techniques, namely Gillespie’s Stochastic Simulation Algorithm (using Kinetiscope) and a discrete Markov chain, have showed the diverse reasons for this failure, including the rate of reaction between the free radicals and the non-enzymatic antioxidants, which is considered a necessary threshold for evaluating the effect of an antioxidant on the free radical defence systems naturally present, making it able to minimise their action [ 63 ].…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
“…Diosmetin is a citrus flavonoid with antioxidant and anti-inflammatory effects. Experimental studies have shown its ability to ameliorate vascular dysfunction and remodelling by influencing the expression of Nrf2/HO-1 and p-JNK/p-NF-κB in hypertensive rats [ 65 ]. Other natural compounds explored in recent examinations include, for example, essential oils, which represent alternatives to natural and synthetic antioxidant agents [ 66 , 67 ].…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
“…Diosmetin is a citrus flavonoid with antioxidant and anti-inflammatory effects. Diosmetin improved hypertension, endothelial dysfunction by modulation of NRF2/HO-1, and p-JNK/p-NF-κB expression in hypertensive rats [ 147 ]. Irisin is an exercise-induced myokine, and it was reported that intravenous injection of irisin in an SHR model reduced BP, plasma norepinephrine, paraventricular nucleus (PVN) levels of neuronal activation, oxidative stress, and inflammation by activating the NRF2 signaling pathway in the hypothalamic paraventricular nucleus [ 148 ].…”
Section: Nrf2 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…NO is a soluble gas with vasodilator promoting functions, as well as anti-inflammatory and antioxidant properties that can play an important role in maintaining vascular homeostasis [ 53 , 54 ]. Decreased production and sensitivity of NO can lead to imbalance of vascular homeostasis and thrombosis, thereby potentially facilitating the progression of AS [ 55 ].…”
Section: Effects Of Probiotics On Traditional As Progression Factorsmentioning
confidence: 99%